Institutional Assessment and the Intellectual Work of Teaching and Learning in First Year Composition - Emily Donnelli-Sallee (Park University, 2013)
Institutional assessment initiatives can provide opportunities to make the intellectual work of teaching and learning in composition studies more visible. Reciprocally, the scholarship of teaching and learning's situatedness within disciplinary norms and values can enhance institutional assessments, providing a check on the tendency to rely on singular, overly generalized mechanisms for capturing course- or program-level data. This article shares one example of the reciprocal relationship that can occur between disciplinary and institutional assessment initiatives.